How visitors of luxury cruises perceive a tourist destination: internal determinants, satisfaction and intention to return - Zeferino, E.C. (2015)
The cruise industry is responding to increasing demand for luxury travel by using more and larger luxurious cruise ships which are now arriving to main maritime ports and to a growing number of new terminals. So, it is important to understand if passengers are satisfied and if they intend to return. Therefore, a survey was conducted nearby the Port of Lisbon in order to capture the perception of international cruise tourists about satisfaction and intention to return. Data collected from a sample of 412 respondents was treated using multiple regression analysis. Findings highlight that it is important to assure that maritime ports as Lisbon can take advantage of these luxury supersized ships and, by consequence, tackle the tourists that arrive from any part of the world, almost every day to Portugal.